Lecturers’ and Learners’ Perceptions on the ’New Headway’Curriculum within the Framework of Higher Education Reform at Erbil Polytechnic University - Othman Ali, Selar; Muhammad Mustafa, Awat; Hassan Azeez, Nadhim (International Journal of Psychosocial Rehabilitation, 2019)
The Ministry of Higher Education and Scientific Research of Kurdistan Regional Government (MoHESR-KRG) initiated a reform policy in order to introduce international standards of quality to higher education. The reform policy aims to enhance the English language curricula. The reform process started in 2009 and the main purpose of the English language reform was to improve students’ language use and skills for academic purposes. This research emphasises the implications of the new curriculum of English language for freshmen learners at Erbil Polytechnic University (EPU). Learners’ perspective on the course content, course objectives, as well as the lecturers’ method of teaching are evaluated through two conducted quantitative questionnaires. In a total of 178 learners, 102 learners responded to the first questionnaire, and 10 lecturers responded to the second questionnaire with approximately similar questions on the topics being investigated. The research concluded that the majority of both the learners and lecturers had positive attitudes on the course book design, content and the methodology adopted for teaching the materials. The results of the study also show that there is a significant improvement in learners’ speaking, listening and reading skills while studying the course materials.